PENGARUH KEPEMIMPINAN, PENGAWASAN SUMBER DAYA MANUSIA, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI KANTOR WILAYAH DJP BENGKULU DAN LAMPUNG DI MASA PANDEMI COVID-19 - Reksa Bila Arista (2022)
This research is a quantitative study with the aim of knowing and proving whether there is influence from leadership, supervision of human resources and compensation on employee performance at the Kantor Wilayah DJP Bengkulu and Lampung during the Covid-19 Pandemic. The sample in this study were 59 employees. The sampling method is a proportionate stratified random sampling technique. Data analysis using the SmartPLS 3.0 application. Testing the hypothesis in this study using the coefficient of determination test, t test, and f test. The results showed that (1) leadership has a positive and significant influence on employee performance, (2) human resource supervision has a positive and significant effect on employee performance, (3) compensation has a positive and significant effect on employee performance, (4) leadership, human resource monitoring, and compensation have a simultaneous influence on employee performance.